Beyond 'safeguarding' and 'empowerment' in Hong Kong: towards a relational model for supporting women who have left their abusive partners - Kong, Sui-Ting (Journal of family violence, 2021)
This project explores the post-separation needs of Chinese women in Hong Kong who have left their abusive partners and how they might be addressed The project aims to provide insights for improving the local domestic violence service, whose main focus is on crisis intervention. Cooperative Grounded Inquiry (CGI) was developed as a novel participatory action research methodology (PAR) for fostering collaboration between social work practitioner-researchers and women service users. Its purpose is to generate useful knowledge and provide support for abused women and their children. The project involved 7 Hong Kong Chinese women as participant-researchers. The inquiry group met at least once a week for 6 months to explore the post-separation needs of the women and their children, and to implement and evaluate the practices/services developed through this project together in a participatory manner. Women participants identified the problems of doing either ‘victim’ or ‘survivor’ that respectively underpin the ‘safeguarding’ and the ‘empowerment’ models; and they developed practices for ‘doing being oneself’ beyond the victim-survivor dichotomy. This paper presents the changing self-narratives of women participants over the research project, from victimhood to survivorhood and from survivorhood to survivor-becoming. These narratives demonstrate the importance of safeguarding women’s space for undertaking symbolic action and of empowering them through using volcabulary that can help them describe themselves/their experiences differently from mainstream discourses. Women’s narratives highlight the existing ‘planetary difference’ between the safeguarding model, which treats women as helpless and vulnerable and in need of external support, and the empowerment model which treats them as powerful, resilient and with resources and solutions to problems. The study transcends the victim-survivor dichotomy and service models by proposing an alternative relational model that emphasises power sharing in making sense of abusive experiences and finding one’s own voice in a supportive community.